Pengembangan model pembelajaran english for specific purposes untuk spa therapists di kawasan wisata kuta - Aryati, Kadek Feni; Parwati, Komang Shanty Muni; Chandra, I Made Krisna Adi (Jurnal Kepariwisataan dan Hospitalitas; Vol 2 No 2 (2018): Vol.2,No.2,2018DO - 10.24843/JKH.2018.v02.i02.p05, 2018)
Abstract The lack of english mastery by Spa Therapists at Kuta become one of the problems in giving maximal service for tourist. This study aims to (1) identify the communication problems faced by Spa therapists in Kuta, (2) analyze the training and learning models of English language based on the needs of Spa therapists in Kuta, and (3) develop ICT-based English learning models for Spa therapist in Kuta. Ten experienced Spa therapists were involved as the resource persons in this study. Other data sources in this study were documents in form of English books for Spa therapists. The data that has been collected was analyzed quantitatively and qualitatively. Based on the results of the analysis, it was found that (1) Spa therapists encountered some obstacles in communicating with tourists due to lack of mastery of English, (2) Spa therapists needed ICT-based English teaching materials to facilitate them in accessing materials, and (3) the teaching materials which developed 12 topics related to communication between Spa therapists and tourists can be accessed through https://-edu.com/spa/ . Teaching materials that have been developed in this study can be used as teaching materials independently by Spa therapists and training instructors as teaching materials. Keywords: ESP, Learning model, Spa Therapists, ICT